(3TQM WGTcHQi RGOI Ydi GdebOeI GdLRQjIs - (3YUGe GdOjf CMeO Hf eUWai GdeYQha HWGTcHQi RGOgs; (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj,J (B833 (3g` s
(3ChdgG (B:s
(3hHYO abO JWGHbJ bGWHI GdYde hcGaI CQHGHkG GdYQaGf Ydi Cf CTQa GdYdhe hCYdGgG Yde GdbQBf s
(3BNQgG (B:s
(3hEPG MSf HfG QO Edi GdfOe hGdEfcGQ hGSJZaQhG Gddg ef TcGjI GdReGf GdebghQ JMJ bOQJ Gdedc GdeSJYGf JeJ GdQSGdI HYhf Gddg Gdedc GdhgGH s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B45 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B291s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs